The Origins of the Urban Crisis : Race and Inequality in Postwar Detroit - Updated Edition - Sugrue, Thomas J., 1962- (Book collections on Project MUSE., 2014)
Once America's "arsenal of democracy," Detroit is now the symbol of the American urban crisis. In this reappraisal of America's racial and economic inequalities, Thomas Sugrue asks why Detroit and other industrial cities have become the sites of persistent racialized poverty. He challenges the conventional wisdom that urban decline is the product of the social programs and racial fissures of the 1960s. Weaving together the history of workplaces, unions, civil rights groups, political organizations, and real estate agencies, Sugrue finds the roots of today's urban poverty in a hidden history o.